VIRTUALITY AND RHIZOMA: BEING AT A CROSSROAD - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The rhizome character of social networks is proved in the article. The main aim and task of our research is the representation in the categories of philosophy of the postmodern process of virtualization of modern social practices in order to identify patterns, trends and contradictions in the development of society as a system of social networks. Research results. To the properties of rhizomes, which determine its essence and potential, the researchers attributed the combination and heterogeneity, plurality, discontinuity, cartography, decalcomania. The listed principles of rhizome function give it unusual properties. Therefore, rhizome is more resistant to transformations, which completely rebuilds both its nature and the nature of its objects. Conclusion. It is proved that in the conditions of the Information society the virtual social space defines a new contour of social interactions, sets new rules of existence for most social practices. It has been established that language games are a means of mitigating the negative effects of the fragmentation of social space.